2015
DOI: 10.2188/jea.je20140186
|View full text |Cite
|
Sign up to set email alerts
|

The Japan Environment and Children’s Study (JECS): A Preliminary Report on Selected Characteristics of Approximately 10 000 Pregnant Women Recruited During the First Year of the Study

Abstract: BackgroundThe Japan Environment and Children’s Study (JECS) is an ongoing nationwide birth cohort study launched in January 2011. In this progress report, we present data collected in the first year to summarize selected maternal and infant characteristics.MethodsIn the 15 Regional Centers located throughout Japan, the expectant mothers were recruited in early pregnancy at obstetric facilities and/or at local government offices issuing pregnancy journals. Self-administered questionnaires were distributed to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
88
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(92 citation statements)
references
References 11 publications
4
88
0
Order By: Relevance
“…The majority of children ( N = 279 [78.2%]) came from a pilot study [Kawamoto et al, ] of a large‐scale on‐going longitudinal birth cohort study (the Japan Environment and Children's Study: JECS) [Kawamoto et al, ] which has been designed to examine the effects of environmental exposures on health from birth to 13 years of age, while the rest ( N = 78) were recruited via community kindergartens or nurseries. The characteristics of the JECS participants (singleton births, gestational age at birth, sex, and birth weight) and maternal age were similar to those found in national survey data on the Japanese general population [Michikawa et al, ]. Families' household income [Michikawa et al, ] was also similar to the national average reported by the Japanese Ministry of Health, Labour and Welfare (http://www.mhlw.go.jp/english/database/db-hss/dl/report_gaikyo_2011.pdf).…”
Section: Methodssupporting
confidence: 67%
See 1 more Smart Citation
“…The majority of children ( N = 279 [78.2%]) came from a pilot study [Kawamoto et al, ] of a large‐scale on‐going longitudinal birth cohort study (the Japan Environment and Children's Study: JECS) [Kawamoto et al, ] which has been designed to examine the effects of environmental exposures on health from birth to 13 years of age, while the rest ( N = 78) were recruited via community kindergartens or nurseries. The characteristics of the JECS participants (singleton births, gestational age at birth, sex, and birth weight) and maternal age were similar to those found in national survey data on the Japanese general population [Michikawa et al, ]. Families' household income [Michikawa et al, ] was also similar to the national average reported by the Japanese Ministry of Health, Labour and Welfare (http://www.mhlw.go.jp/english/database/db-hss/dl/report_gaikyo_2011.pdf).…”
Section: Methodssupporting
confidence: 67%
“…The characteristics of the JECS participants (singleton births, gestational age at birth, sex, and birth weight) and maternal age were similar to those found in national survey data on the Japanese general population [Michikawa et al, ]. Families' household income [Michikawa et al, ] was also similar to the national average reported by the Japanese Ministry of Health, Labour and Welfare (http://www.mhlw.go.jp/english/database/db-hss/dl/report_gaikyo_2011.pdf). In terms of the current study all of these children were assumed to be representative of the general child population.…”
Section: Methodssupporting
confidence: 67%
“…Eligibility criteria for expectant mothers were as follows: that they (i) resided at the time of recruitment in any of the study areas selected by 15 Regional JECS Centers located countrywide, (ii) had an expected delivery date after August 1, 2011, and (iii) were capable of comprehending the Japanese language and completing the self‐administered questionnaire . The sample size has been calculated in the JECS protocol by the Ministry of the Environment .…”
Section: Methodsmentioning
confidence: 99%
“…We have conducted the nationwide population‐based birth cohort study known as the “Japan Environment and Children’s Study (JECS)” planned by the Ministry of the Environment, Government of Japan . The study subjects consisted of 104 102 registered pregnancies recruited during the first 3 years of the JECS, and their babies are now being followed up for 13 years mainly to examine the influence of the uterine environment on the fetus.…”
Section: Introductionmentioning
confidence: 99%
“…We have conducted a nationwide prospective birth cohort study, the Japan Environment and Children's Study (JECS), which was planned by the Ministry of the Environment, Government of Japan. [15][16][17][18][19] The study comprises 104 102 registered prenatal records and the delivered children will be followed up until they reach 13 years of age to investigate the effect of environment, especially during the fetal period, on the health of babies and their subsequent growth and health. The present study assessed the association of weekly working hours and frequency of night shifts during pregnancy with pregnancy and perinatal outcomes.…”
Section: Introductionmentioning
confidence: 99%